Power flow in distribution networks with earth return - Ciric, R. M.; Ochoa, L. F.; Padilha, A. (Elsevier B.V., 2004)
The problems of wave propagation and power flow in the distribution network composed of an overhead wire parallel to the surface of the ground have not been satisfactorily solved. While a complete solution of the actual problem is impossible, as it is explained in the famous Carson's paper (1926), the solution of the problem, where the actual earth is replaced by a plane homogenous semi-infinite solid, is of considerable interest. In this paper, a power flow algorithm in distribution networks with earth return, based on backward-forward technique, is discussed. In this novel use of the technique, the ground is explicitly represented. In addition, an iterative method for determining impedance for modelling ground effect in the extended power flow algorithm is suggested. Results obtained from single-wire and three-wire studies using IEEE test networks are presented and discussed. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: distribution networks; single-wire with earth return; three-wire system with earth return; power flow